The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10489-020-01902-1
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning based detection and analysis of COVID-19 on chest X-ray images

Abstract: Covid-19 is a rapidly spreading viral disease that infects not only humans, but animals are also infected because of this disease. The daily life of human beings, their health, and the economy of a country are affected due to this deadly viral disease. Covid-19 is a common spreading disease, and till now, not a single country can prepare a vaccine for COVID-19. A clinical study of COVID-19 infected patients has shown that these types of patients are mostly infected from a lung infection after coming in contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
294
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(302 citation statements)
references
References 44 publications
2
294
0
6
Order By: Relevance
“…Also, to demonstrate the efficacy of the proposed ensemble based algorithm, a comparison of the proposed algorithm with a number of recent works on COVID detection using Chest X-Ray images have been presented in Table 4. It can be observed that the proposed method integrates the capabilities of state-of-the-art deep learning models to yield comparable or better results that the works where vanilla state-of-the-art deep learning models have been used [12,27,28]. Some of the new methods [29][30][31] show very promising results, though they may suffer from criticism due to the small size of the data used in the experimental set-up.…”
Section: Experiments and Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Also, to demonstrate the efficacy of the proposed ensemble based algorithm, a comparison of the proposed algorithm with a number of recent works on COVID detection using Chest X-Ray images have been presented in Table 4. It can be observed that the proposed method integrates the capabilities of state-of-the-art deep learning models to yield comparable or better results that the works where vanilla state-of-the-art deep learning models have been used [12,27,28]. Some of the new methods [29][30][31] show very promising results, though they may suffer from criticism due to the small size of the data used in the experimental set-up.…”
Section: Experiments and Resultsmentioning
confidence: 83%
“…There have been multiple works done by researchers in the area of COVID-19 patient detection using CXR images [4,5,7,12,[26][27][28][29][30][31][32]. In one such work by Makris et al [4], transfer learning has been used with the Inception-v3 network to classify normal, pneumonia and COVID-19 patients using CXR images.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of human reasoning is accommodated by the ProtoPNet model, where comparison of image parts with learned prototypes is integral to the reasoning process of the model. Recently, some deep learning/machine learning models have been developed to classify the X-ray images of Covid-19 patients, normal people and pneumonia patients, see [1], [7], [16], [17], [19], [25], [28], [44]. A survey article is also written that summarizes the research works related to deep learning applications on COVID-19 medical image processing [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…4 ). Like other pneumonia types, a CT scan may be a reliable test for screening SARS-COV 2 cases [ 184 , 185 ]. However, the analysis required specialized equipment and failed to meet a large scale of requirement, and it may not provide benefit for point-of-care (POC) diagnosis of COVID-19.…”
Section: Introductionmentioning
confidence: 99%